Structure–reactivity relationship of Amadori rearrangement products compared to related ketoses. (16th June 2016) - Kaufmann, Martin; Meissner, Philipp M.; Pelke, Daniel; Mügge, Clemens; Kroh, Lothar W.
Highlights: Sugar degradation kinetics are related to isomerisation dynamics. Amadori rearrangement products show complex isomerisation/mutarotation. Isomerisation rates depend on C-1 substituent mediated intramolecular catalysis. Fast 5 C2 ↔ 2 C5 ring inversion occurs in case ofd -fructose-derived α-pyranoses. Graphical abstract: Abstract: Structure-reactivity relationships of Amadori rearrangement products compared to their related ketoses were derived from multiple NMR spectroscopic techniques. Besides structure elucidation of six Amadori rearrangement products derived fromd -glucose andd -galactose withl -alanine, l -phenylalanine andl -proline, especially quantitative 13 C selective saturation transfer NMR spectroscopy was applied to deduce information on isomeric systems. It could be shown exemplarily that the Amadori compound N -(1-deoxy-d -fructos-1-yl)-l -proline exhibits much higher isomerisation rates thand -fructose, which can be explained by C-1 substituent mediated intramolecular catalysis. In combination with a reduced carbonyl activity of Amadori compounds compared to their related ketoses which results in an increased acyclic keto isomer concentration, the results on isomerisation dynamics lead to a highly significant increased reactivity of Amadori compounds. This can be clearly seen, comparing approximated carbohydrate milieu stability time constants ( ACuSTiC ) which is 1 s for N -(1-deoxy-d -fructos-1-yl)-l -proline and 10 s ford -fructose at pD 4.20 ± 0.05 at 350 K. In addition, first NMR spectroscopic data are provided, which prove that α-pyranose of (amino acid substituted)d -fructose adopts both, 2 C5 and 5 C2 conformation.